1994
DOI: 10.1007/bf01784330
|View full text |Cite
|
Sign up to set email alerts
|

The stable prostacyclin analogue Cicaprost inhibits metastasis to lungs and lymph nodes in the 13762NF MTLn3 rat mammary carcinoma

Abstract: Prostacyclin and its stable analogues have been shown to interfere specifically with certain steps of the metastatic cascade. The antimetastatic activity of the stable prostacyclin analogue Cicaprost (Schering AG) on haematogenous metastasis in a series of tumours in rats and mice has been well established. In order to test the effect of Cicaprost on lymphogenous metastasis we chose the metastatic cell clone MTLn3 derived from the 13762NF rat mammary carcinoma. The effect of Cicaprost on prevention of lung met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…48 Additional studies revealed that cicaprost, a metabolically stable and orally active analogue of prostacyclin, has prominent antimetastatic effects in a series of spontaneously metastasising mammary carcinomas of experimental animals (rat, mouse) and it reduce the median number of metastases from other tumor types. 93,95,96 The mechanism of action of cicaprost is different from cytostatic drugs, because primary tumor growth in vivo or proliferation in vitro remained unchanged. Finally, cicaprost can be used in combination with cytostatic drugs (cyclophosphamide, doxorubicin or 5-FU), without interfering with inhibition of tumor growth.…”
Section: Role Of a Nticoagulants And I Nhibitors Of P Latelet A Ggregmentioning
confidence: 99%
See 1 more Smart Citation
“…48 Additional studies revealed that cicaprost, a metabolically stable and orally active analogue of prostacyclin, has prominent antimetastatic effects in a series of spontaneously metastasising mammary carcinomas of experimental animals (rat, mouse) and it reduce the median number of metastases from other tumor types. 93,95,96 The mechanism of action of cicaprost is different from cytostatic drugs, because primary tumor growth in vivo or proliferation in vitro remained unchanged. Finally, cicaprost can be used in combination with cytostatic drugs (cyclophosphamide, doxorubicin or 5-FU), without interfering with inhibition of tumor growth.…”
Section: Role Of a Nticoagulants And I Nhibitors Of P Latelet A Ggregmentioning
confidence: 99%
“…Finally, cicaprost can be used in combination with cytostatic drugs (cyclophosphamide, doxorubicin or 5-FU), without interfering with inhibition of tumor growth. 94,96 Experimental and clinical studies suggest that heparin and vitamin K antagonists are effective compounds for the prevention of metastases. 33,107 Data from randomised trials suggest that small-cell lung cancer (SCLC) consistently responds to heparin and vitamin K antagonist, but several other tumors, including non small-cell cancer (NSCLC), colon and prostate cancer, do not respond to warfarin 13,11,55,111,117 and do not produce thrombin.…”
Section: Role Of a Nticoagulants And I Nhibitors Of P Latelet A Ggregmentioning
confidence: 99%
“…The lung weight was decreased significantly by the two higher doses used (Figure 3). Concerning lymph node metastasis, cicaprost reduced the weight of the ipsilateral axillary lymph nodes to about 50% at all three doses used and the weight of the contralateral lymph nodes to the level of a nontumor bearing animal ( Figure 3) [15].…”
Section: Effect On Experimental Mammary Carcinomasmentioning
confidence: 99%
“…We have shown a correlation of the presence of functional prostacyclin receptors and antimetastatic effects in vivo and in vitro. In vivo, cicaprost exerts a prominent antimetastatic action on MTLn3 mammary carcinomas [15], which have functional prostacyclin receptors, but has no effect on RUCA endometrial carcinomas, which lack functional receptors. In vitro, transendothelial migration of MTLn3 cells is inhibited by cicaprost [19].…”
Section: Mechanism Of Actionmentioning
confidence: 99%